Intranasal steroids versus placebo or no intervention for chronic rhinosinusitis - Chong, Lee Yee; Head, Karen; Hopkins, Claire; Philpott, Carl; Schilder, Anne G M; Burton, Martin J (Cochrane database of systematic reviews, 2016)
This review is one of six looking at the primary medical management options for patients with chronic rhinosinusitis.Chronic rhinosinusitis is common and is characterised by inflammation of the lining of the nose and paranasal sinuses leading to nasal blockage, rhinorrhoea, facial pressure/pain and loss of sense of smell. The condition can occur with or without nasal polyps. The use of topical (intranasal) corticosteroids has been widely advocated for the treatment of chronic rhinosinusitis given the belief that inflammation is a major component of this condition. To assess the effects of intranasal corticosteroids in people with chronic rhinosinusitis. The Cochrane ENT Information Specialist searched the Cochrane ENT Trials Register; Central Register of Controlled Trials (CENTRAL 2015, Issue 8); MEDLINE; EMBASE; ClinicalTrials.gov; ICTRP and additional sources for published and unpublished trials. The date of the search was 11 August 2015. Randomised controlled trials (RCTs) with a follow-up period of at least three months comparing intranasal corticosteroids (e.g. beclomethasone dipropionate, triamcinolone acetonide, flunisolide, budesonide) against placebo or no treatment in patients with chronic rhinosinusitis. We used the standard methodological procedures expected by Cochrane. Our primary outcomes were disease-specific health-related quality of life (HRQL), patient-reported disease severity and the commonest adverse event - epistaxis. Secondary outcomes included general HRQL, endoscopic nasal polyp score, computerised tomography (CT) scan score and the adverse events of local irritation or other systemic adverse events. We used GRADE to assess the quality of the evidence for each outcome; this is indicated in italics. We included 18 RCTs with a total of 2738 participants. Fourteen studies had participants with nasal polyps and four studies had participants without nasal polyps. Only one study was conducted in children. Intranasal corticosteroids versus placebo or no intervention Only one study (20 adult participants without polyps) measured our primary outcome disease-specific HRQL using the Rhinosinusitis Outcome Measures-31 (RSOM-31). They reported no significant difference (numerical data not available) (very low quality evidence).Our second primary outcome, disease severity , was measured using the Chronic Sinusitis Survey in a second study (134 participants without polyps), which found no important difference (mean difference (MD) 2.84, 95% confidence interval (CI) -5.02 to 10.70; scale 0 to 100). Another study (chronic rhinosinusitis with nasal polyps) reported an increased chance of improvement in the intranasal corticosteroids group (RR 2.78, 95% CI 1.76 to 4.40; 109 participants). The quality of the evidence was low.Six studies provided data on at least two of the individual symptoms used in the EPOS 2012 criteria to define chronic rhinosinusitis (nasal blockage, rhinorrhoea, loss of sense of smell and facial pain/pressure). When all four symptoms in the EPOS criteria were available on a scale of 0 to 3 (higher = more severe symptoms), the average MD in change from baseline was -0.26 (95% CI -0.37 to -0.15; 243 participants; two studies; low quality evidence). Although there were more studies and participants when only nasal blockage and rhinorrhoea were considered (MD -0.31, 95% CI -0.38 to -0.24; 1702 participants; six studies), the MD was almost identical to when loss of sense of smell was also considered (1345 participants, four studies; moderate quality evidence).When considering the results for the individual symptoms, benefit was shown in the intranasal corticosteroids group. The effect size was larger for nasal blockage (MD -0.40, 95% CI -0.52 to -0.29; 1702 participants; six studies) than for rhinorrhoea (MD -0.25, 95% CI -0.33 to -0.17; 1702 participants; six studies) or loss of sense of smell (MD -0.19, 95% CI -0.28 to -0.11; 1345 participants; four studies). There was heterogeneity in the analysis for facial pain/pressure (MD -0.27, 95% CI -0.56 to 0.02; 243 participants; two studies). The quality of the evidence was moderate for nasal blockage, rhinorrhoea and loss of sense of smell, but low for facial pain/pressure.There was an increased risk of epistaxis with intranasal corticosteroids (risk ratio (RR) 2.74, 95% CI 1.88 to 4.00; 2508 participants; 13 studies; high quality evidence).Considering our secondary outcome, general HRQL, one study (134 participants without polyps) measured this using the SF-36 and reported a statistically significant benefit only on the general health subscale. The quality of the evidence was very low.It is unclear whether there is a difference in the risk of local irritation (RR 0.94, 95% CI 0.53 to 1.64; 2124 participants; 11 studies) (low quality evidence).None of the studies treated or followed up patients long enough to provide meaningful data on the risk of osteoporosis or stunted growth (children). Other comparisons We identified no other studies that compared intranasal corticosteroids plus co-intervention A versus placebo plus co-intervention A. Most of the evidence available was from studies in patients with chronic rhinosinusitis with nasal polyps. There is little information about quality of life (very low quality evidence). For disease severity, there seems to be improvement for all symptoms (low quality evidence), a moderate-sized benefit for nasal blockage and a small benefit for rhinorrhoea (moderate quality evidence). The risk of epistaxis is increased (high quality evidence), but these data included all levels of severity; small streaks of blood may not be a major concern for patients. It is unclear whether there is a difference in the risk of local irritation (low quality evidence).